Organizational Culture Role in Linking Tqm Practices to Performance in the Yemen Oil and Gas Sector - Qais Ahmed Almaamari; Al-Baraa Abdulrahman Al-Mekhlafi; Noreen Kanwal; Mohammed I. F. Dawwas (Taylor & Francis Online, 2025)
Indexed Publication (Tier 2)